Learning Vocabulary Through Listening: The Role of Vocabulary Knowledge and Listening Proficiency. Issue 4 (4th June 2020) - Zhang, Pengchong; Graham, Suzanne
Abstract: This study explored the impact of preexisting vocabulary knowledge (PVK) and listening proficiency on the vocabulary learning through listening of 137 Chinese learners of English, when provided with three types of oral vocabulary explanations—second language (L2), codeswitching (CS), and contrastive focus‐on‐form (CFoF)—and when no explanations (NE) were provided (extending Zhang & Graham, 2019). Listening proficiency was a more important factor influencing vocabulary learning through aural input than PVK was, with most notable gains for learners with high listening proficiency and low PVK. The CFoF approach was the most helpful for learners regardless of their PVK and listening proficiency, whereas the NE approach was the least helpful. Moreover, comparing just the CS and L2 groups, the CS approach was more helpful for lower PVK learners and for more proficient listeners than the L2 approach was. Higher PVK learners and less proficient listeners, however, benefited more from the L2 approach than from the CS approach. The study highlights the complex interplay of vocabulary knowledge, listening proficiency, and instructional conditions, factors useful to bear in mind when planning activities to enhance vocabulary learning through listening. Abstract :